PERBANDINGAN DIAMETER PISTON 57 MM, 59 MM DAN 62 MM TERHADAP KONSUMSI BAHAN BAKAR SEPEDA MOTOR YAMAHA VIXION 150 CC TAHUN 2012 - Wahyu Romadlhon, Ahmad; Budiyono, Budiyono; Feriansah, Arif (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2020)
The comparison of pistons with a diameter of 57 mm, 59 mm and 62 mm is able to increase the cc of the Yamaha Vixion motorcycle where the piston with a diameter of 57 mm can produce 150 cc while the piston with a diameter of 59 mm can produce 160 cc and for a piston with a diameter of 62 mm it can produce 177 cc. One of the efforts to determine the fuel efficiency of a motor vehicle is to use the tank drain method or the full to full method. The method I use is the tank drain method. Because the difference between the piston diameters can increase power and torque, it is certain that the effect of changing between piston diameters also affects fuel consumption. This study aims to determine the ratio of the piston diameter to the fuel consumption efficiency of Yamaha Vixion motorcycles where this test starts from idle rotation, and variations in piston diameter (57 mm), (59 mm) and (62 mm). Pertamax 500 ml, 1000 ml and 1500 ml were tested on the streets. Based on the test results, it was found that the piston with a diameter of 57 mm was able to cover a distance of 37.53 km by consuming 1000 ml of fuel while the piston with a diameter of 59 mm was able to cover a distance of 22.98 km by consuming 1000 ml of fuel, while the piston with a diameter of 62 mm able to cover a distance of 16.65 km by consuming 1000 ml of fuel.Keywords: Piston diameter, cylinder block, fuel efficiency